2015
DOI: 10.1099/vir.0.000168
|View full text |Cite
|
Sign up to set email alerts
|

Delayed IFN response differentiates replication of West Nile virus and Japanese encephalitis virus in human neuroblastoma and glioblastoma cells

Abstract: West Nile virus (WNV) and Japanese encephalitis virus (JEV) are important causes of human encephalitis cases, which result in a high mortality ratio and neurological sequelae after recovery. Understanding the mechanism of neuropathogenicity in these viral infections is important for the development of specific antiviral therapy. Here, we focused on human-derived neuronal and glial cells to understand the cellular responses against WNV and JEV infection. It was demonstrated that early IFN-b induction regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Astrocytic activation and inflammatory factor release is an important mechanism of Japanese encephalitis virus (10). In vitro cultured glial cells were transfected with the virus, the virus titer was not high, and affected the detection of inflammatory markers (11).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytic activation and inflammatory factor release is an important mechanism of Japanese encephalitis virus (10). In vitro cultured glial cells were transfected with the virus, the virus titer was not high, and affected the detection of inflammatory markers (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, JEV infection of HeLa cells showed an earlier IFN induction pattern [68]. Additionally, in a more recent study the authors observed that the presence of the viral-derived RNA in the cytoplasm at the early stages of infection, and therefore the timing of IFN induction, depends on the cell type used for their experiment [72]. Altogether, this suggests that differences in RNA leaking from the vesicles to the cytosol among cell lines could be influenced by a cell type-specific conformation of the double-membrane vesicles or other host factors.…”
Section: Antagonism Of Type I Ifn Productionmentioning
confidence: 99%
“…The production of IFN‐α/β through pattern recognition receptors, along with consequent induction of ISG15, is crucial to the control of JEV replication throughout the course of infection. However, the coordinated induction of SOCS expression, along with protein tyrosine phosphatase activity via both JEV nonstructural protein‐related and yet unidentified mechanisms, causes variable efficiency in restricting JEV replication . Results of Western blot have revealed that differentiated PC12 cells were ineffective in inducing tyrosine phosphorylation of Jak1, Stat1 and Stat2 or were able to cause a rapid drop of tyrosine phosphorylation of Jak1, Stat1 and Stat2, as compared to naïve cells after JEV infection.…”
Section: Discussionmentioning
confidence: 99%